Kabbalah, Symbolism and Metaphysics in Russian Freemasonry of the XVIIIth – XIXth centuries - Khalturin, Yuriy (2015)
This paper considers some connections between Kabbalah and Freemasonry in Russia as reflected in the archives of the Department of Manuscripts of the Russian State Library (DMS RSL). The link between them was based on the understanding of both Kabbalah and Freemasonry as symbolic philosophy and “true metaphysics”. In the article we show how Russian Freemasons adopted Kabbalistic doctrines of Ein-Soph, Sephiroth, Adam Kadmon and mixed them with Neoplatonism’s theory of emanation, Christian apophatic mysticism, hermetic and alchemical worldview, and Christian sophiology. This eclectic adaptation was based on the interpretation of such masonic symbols as the point in a circle, Jachin and Boaz columns, and the Flaming Star. Masonic symbolism allowed for the combination of different esoteric doctrines in one unified worldview to make masonic symbols more attractive to the “educated milieu” of Russian nobility.